Abdominal center strength training in table tennis players - Liu, K. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: A series of reforms in table tennis involving the development trend of table tennis technology and the needs of athletes to improve competitive ability and prevent injuries have presented new requirements for the abdominal center strength of athletes. Objective: Study the impacts of implementing abdominal center strength training on the training of table tennis players. Methods: A broad literature search and experimental comparison were performed. Twenty professional athletes aged 14 to 20 from the men's table tennis team were selected as volunteers for the research, divided into two groups according to the mean, standard deviation, and results of special technical tests. An independent sample t-test was performed on both groups. Results: Significant differences were found for abdominal control, for legs and arms crossed on both ends, for supine posture, and for leg raising (P<0.05). Conclusion: Abdominal center strength training can effectively improve the special ability level of young table tennis players, improve the body control ability in players, and the stability of the shot action.